Environmental Challenges in Indonesia: An Emerging Issue in the Social Study of Religion - Frans Wijsen (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2021)
One of the emerging issues in religious studies is the relationship between religion and the environment. This issue has conceptual, empirical, and practical dimensions. This article explores some of the completed and ongoing empirical research projects and asks what a social study of religion can contribute to the theory and practice of environmentalism in Indonesia, and what this signifies for future research in this field. It argues that the social study of religion can help to conceptualize religion as a social construct and move beyond reified understandings of religion. Scholars of religion can make them aware of the fact that on the one hand religion has an added value and makes a difference, and that on the other hand religion is complex, diverse, and ambiguous. For future research in this field, the article proposes to elaborate more on the ambivalence of religion and to use the dialogical self-theory to deal with the dilemma between norms and practices, the tension between theological and technological voices, the faith-based underpinnings of ‘small’ (‘back to nature’) and ‘smart’ (circular economy, green technology) solutions for ecological challenges, and the gap between the religion that is lived in every-day lives and the religion that is learned in schools and mosques, drawing on classical sources.